Democracy, Good Governance and Development in Nigeria: A Survey of Karu Local Area - Audi, Ahmed Abubakar; Salisu, Ibrahim Isah; Zakari, Musa (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
The study is examines democracy, good governance and development in Nigeria: a survey of Karu Local Area .  Social contract theory was used as theoretical framework. The study adopted survey research method; data was collected from the primary and secondary sources. The study reveals that Democracy has enhanced good governance and development for the people in Keffi Local Government. Karu Local Government council to some extent has provided the people of Karu Local Government Area with social amenities like roads, pipe born water, functional hospital, schools and others essential service for the citizens. The study recommends that Elected and Caretaker Management of Karu Local Government Council should consolidate on the effort made so far by the provision of more physical infrastructures like roads, bridges, potable water, telecommunications and public transport to remote villages that are yet to feel the dividends of democracy. Keywords: Democracy, Governance, Good Governance, Development